Incidencia del comercio exterior sobre el crecimiento económico, un estudio econométrico para países de América Latina, periodo 1990-2020 - Caraguay Caraguay, Edison Fernando (2023)
The priority for any economy in the world is economic wellbeing, and one of the factors to achieve it is foreign trade activities, which is the main means that explains long-term growth, given that it enables the accumulation of the production factor: human and physical capital and technological innovation. Thus, this research seeks to analyze the evolution and incidence between foreign trade and economic growth in Latin American countries, period 1990-2020. The study included 15 countries with information available from the World Bank's World Development Indicators (WDI). Statistical tools and econometric strategies with panel data were used. The results indicate that foreign trade has a positive relationship with economic growth in the long run. In addition, a unidirectional causality between GDP and foreign trade is evident. Finally, it is concluded that foreign trade in Latin America does have an impact on economic growth in the long run. It is essential that foreign trade processes be accompanied by greater internal and external investment in science and technology, which would have an impact on the productive matrix of Latin American countries.